Aktivisme Hoofdbestuur Muhammadiyah Bagian PKO di Yogyakarta Sebagai Representasi Gerakan Pelayanan Sosial Masyarakat Sipil (1920-1931) - Ghifari Yuristiadi (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2015)
Penolong Kesengsaraan Oemoem (PKO) was one of the four first organizational divisions formed by Hoofdbestuur Muhammadiyah in 1920. In particular, as the name suggests, this division was expected to design, manage, and develop Muhammadiyah’s social services. Chaired by Hadji Soedjak, in the period 1920- 1931, the PKO had opened a health clinic (1923) and founded the poor house (1923) and orphanages (1931). Muhammadiyah was an organization formally recognized by the Dutch colonial government since 1914, and therefore, the social activities carried the PKO of Hoofdbestuur Muhammadiyah can be seen as a movement of civil society outside the state. It can be said that Muhammadiyah’s widespread social services represented by PKO, became a resource for Muhammadiyah to put its bargaining position in face of the Dutch colonial government, and Kasultanan Yogyakarta and that of Kadipaten Pakualaman. Muhammadiyah provided the social services to the society when the states absent to put on it.